2010
DOI: 10.1071/en09091
|View full text |Cite
|
Sign up to set email alerts
|

Roles of dissolved organic matter in the speciation of mercury and methylmercury in a contaminated ecosystem in Oak Ridge, Tennessee

Abstract: Environmental context. Mercury (Hg) presents an environmental concern owing to its transformation to the potent neurotoxin methylmercury (CH3Hg+). The environmental factors that control bacterial methylation of mercury are poorly understood, but we know that methylmercury is bioaccumulated and biomagnified in aquatic food webs. We show that, even at low concentrations (~3 mg L–1), natural dissolved organic matter strongly complexes with ionic Hg2+ and CH3Hg+, thereby influencing biological uptake and methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 49 publications
2
121
0
Order By: Relevance
“…[95,96] There are other interactions between the organic carbon and Hg cycles that are not as well understood. For example, DOM may provide stabilising ligands to maintain Hg in dissolved form, [97] and C-DOM absorbs UV radiation and thus provides an important control on photo-reduction and other photo-initiated processes in surface water. [15,56] In saline waters, organic compounds produced by algae are able to promote oxidation of Hg 0 even under dark conditions.…”
Section: Microbial Carbon Processing and Mercury In The Arcticmentioning
confidence: 99%
“…[95,96] There are other interactions between the organic carbon and Hg cycles that are not as well understood. For example, DOM may provide stabilising ligands to maintain Hg in dissolved form, [97] and C-DOM absorbs UV radiation and thus provides an important control on photo-reduction and other photo-initiated processes in surface water. [15,56] In saline waters, organic compounds produced by algae are able to promote oxidation of Hg 0 even under dark conditions.…”
Section: Microbial Carbon Processing and Mercury In The Arcticmentioning
confidence: 99%
“…The high Hg contamination in East Fork Poplar Creek (EFPC) located in the ORR area at Oak Ridge, TN, has raised concern among researchers due to the accidentally discharged and spilled Hg from the Y-12 Plant into the surrounding environment in the 1950s . Dong et al (2010) reported high concentration of MeHg in EFPC and found that neither total Hg nor dissolved inorganic Hg concentrations correlate with MeHg concentration in EFPC water. This suggests that speciation, mobility, and accumulation of Hg in EFPC are controlled by site aquatic, and geochemical characteristics, and conditions (Dong et al, 2010).…”
Section: Approachmentioning
confidence: 89%
“…Dong et al (2010) reported high concentration of MeHg in EFPC and found that neither total Hg nor dissolved inorganic Hg concentrations correlate with MeHg concentration in EFPC water. This suggests that speciation, mobility, and accumulation of Hg in EFPC are controlled by site aquatic, and geochemical characteristics, and conditions (Dong et al, 2010).…”
Section: Approachmentioning
confidence: 89%
See 2 more Smart Citations